2008
DOI: 10.1590/s0037-86822008000600006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological study of leprosy cases in the University Hospital of Brasília: 20 years - 1985 to 2005

Abstract: Hansen's disease, also known as leprosy, is an infectious disease still prevalent in Brazil. It is a chronic illness with acute immunological phenomena known as leprosy reactions. In the Federal District of Brazil, the University Hospital of Brasília is the reference centre for leprosy care. The study aimed to characterize the clinical and epidemiological profile of Hansen's disease patients at the University Hospital of Brasília, by descriptive, retrospective analysis of 1,124 patients over the period from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 16 publications
1
34
1
5
Order By: Relevance
“…Demographic data indicated that patients during this period were mostly women, in contrast with previous reports in the literature, which generally shows a predominance of leprosy in men [Feuth et al, 2008;Penna et al, 2008;Ranque et al, 2007]. However, another study did not find differences in the prevalence of the disease in relation to gender [Penna et al, 2008].…”
Section: Analysis Of Clinical Data From Leprosy Patients In a Referencontrasting
confidence: 81%
See 3 more Smart Citations
“…Demographic data indicated that patients during this period were mostly women, in contrast with previous reports in the literature, which generally shows a predominance of leprosy in men [Feuth et al, 2008;Penna et al, 2008;Ranque et al, 2007]. However, another study did not find differences in the prevalence of the disease in relation to gender [Penna et al, 2008].…”
Section: Analysis Of Clinical Data From Leprosy Patients In a Referencontrasting
confidence: 81%
“…Smear examination shows a large number of bacteria, which are also responsible for the strong positivity of serum antibodies against PGL-I (80-100%). LL patients possess a large number of bacilli in the nasal passages and can represent a source of transmission and perpetuation of the disease until adequate and full treatment is provided [Bakker et al, 2006;Britton and Lockwood, 2004;Lockwood et al, 2007;Moura et al, 2008;Penna et al, 2008].…”
Section: Diagnostics and Clinical Forms Of Leprosymentioning
confidence: 99%
See 2 more Smart Citations
“…Seu agente etiológico é o Mycobacterium leprae 1 um bacilo ácido álcool resistente (BAAR) 1,2 . O Brasil apresentou uma prevalência de 1,56 para 10.000 habitantes em 2010, ocupando o segundo lugar mundial em número de casos 2,3,4 .…”
Section: Introductionunclassified